WTO agriculture negotiations : implications for the global South - Clapp, Jennifer (2006)
Analyzes the role of developing countries in the politics of the Doha negotiations on agriculture. Traces the rise of developing country groupings and outlines their bargaining positions and impacts on the talks in relation to the USA and the EU.